Structural and Functional Brain Abnormalities in Mouse Models of Lafora Disease - Burgos, Daniel F. (Int J Mol Sci, 2020)
Mutations in the EPM2A and EPM2B genes, encoding laforin and malin proteins respectively, are responsible for Lafora disease, a fatal form of progressive myoclonus epilepsy with autosomal recessive inheritance. Neuroimaging studies of patients with Lafora disease have shown different degrees of brain atrophy, decreased glucose brain uptake and alterations on different brain metabolites mainly in the frontal cortex, basal ganglia and cerebellum. Mice deficient for laforin and malin present many features similar to those observed in patients, including cognitive, motor, histological and epileptic hallmarks. We describe the neuroimaging features found in two mouse models of Lafora disease. We found altered volumetric values in the cerebral cortex, hippocampus, basal ganglia and cerebellum using magnetic resonance imaging (MRI). Positron emission tomography (PET) of the cerebral cortex, hippocampus and cerebellum of Epm2a(−/−) mice revealed abnormal glucose uptake, although no alterations in Epm2b(−/−) mice were observed. Magnetic resonance spectroscopy (MRS) revealed significant changes in the concentration of several brain metabolites, including N-acetylaspartate (NAA), in agreement with previously described findings in patients. These data may provide new insights into disease mechanisms that may be of value for developing new biomarkers for diagnosis, prevention and treatment of Lafora disease using animal models.